Kosovo - Youth in Jeopardy : Being Young, Unemployed, and Poor in Kosovo - World Bank (Washington, DC, 2012)
The main objective of the report is to provide diagnosis on youth employment, which can provide the basis for future policy design. The report is structured as follows: the chapter one provides a general background of macroeconomic and employment outcomes in Kosovo. The chapter then explains the framework, scope, and limitations of this study (Why youth? Why youth in jeopardy?). Chapter two develops a youth employment profile using data from the 2003-2006 labor force surveys and the 2006 household budget survey; analysis includes a profile of youth in jeopardy in Kosovo, employment trends, and assessment of youth employment quality and constraints. Chapter three provides an overview of the current youth programs and policies being implemented in the territory in the context of the Kosovo Youth National Action Plan (KYNAP).